An empirically derived short form of the Hypoglycaemia Fear Survey II. Issue 4 (9th July 2016) - Grabman, J.; Vajda Bailey, K.; Schmidt, K.; Cariou, B.; Vaur, L.; Madani, S.; Cox, D.; Gonder‐Frederick, L.
Abstract: Aims: To develop an empirically derived short version of the Hypoglycaemia Fear Survey II that still accurately measures fear of hypoglycaemia. Methods: Item response theory methods were used to generate an 11‐item version of the Hypoglycaemia Fear Survey from a sample of 487 people with Type 1 or Type 2 diabetes mellitus. Subsequently, this scale was tested on a sample of 2718 people with Type 1 or insulin‐treated Type 2 diabetes taking part in DIALOG, a large observational prospective study of hypoglycaemia in France. Results: The short form of the Hypoglycaemia Fear Survey II matched the factor structure of the long form for respondents with both Type 1 and Type 2 diabetes, while maintaining adequate internal reliability on the total scale and all three subscales. The two forms were highly correlated on both the total scale and each subscale (Pearson's R > 0.89). Conclusions: The short form of the Hypoglycaemia Fear Survey II is an important first step in more efficiently measuring fear of hypoglycaemia. Future prospective studies are needed for further validity testing and exploring the survey's applicability to different populations. What's new?: Extensive research shows that fear of hypoglycaemia can negatively affect quality of life and diabetes management. The Hypoglycaemia Fear Survey II (HFS‐II) is the most studied and utilized instrument to measure fear of hypoglycaemia, but the length of the survey sometimes limits its utility. This study is the first to generate and validate a short form of the HFS‐II, which will enable expanded investigation of fear of hypoglycaemia and its associated outcomes in clinical and research settings.